Dogs & puppies learn to draw and color 25 favorite dog breeds, step by easy step, shape by simple shape! - Fisher, Diana (Laguna Hills, Calif Walter Foster, 2004)
Using step-by-step instructions, shows how to draw a variety of dogs, including the chihuahua, golden retriever, and dachshund
1
Keywords: Dogs in art; Drawing -- Technique